ChemInform Abstract: Modular Synthesis of Polyene Side Chain Analogues of the Potent Macrolide Antibiotic Etnangien by a Flexible Coupling Strategy Based on Hetero‐bis‐metalated Alkenes. Issue 30 (4th July 2013) - Altendorfer, Mario; Raja, Aruna; Sasse, Florenz; Irschik, Herbert; Menche, Dirk
Abstract Hetero‐bis‐metalated alkenes (I) are used as building blocks for preparation of functionalized oligo‐enes by established coupling procedures.